Chromatin proteomics reveals novel combinatorial histone modification signatures that mark distinct subpopulations of macrophage enhancers - Soldi, Monica; Sigismondo, Gianluca (Nucleic acids research, 2017)
Abstract. The integrated activity of cis-regulatory elements fine-tunes transcriptional programs of mammalian cells by recruiting cell type-specific as well as ubiquitous transcription factors (TFs). Despite their key role in modulating transcription, enhancers are still poorly characterized at the molecular level, and their limited DNA sequence conservation in evolution and variable distance from target genes make their unbiased identification challenging. The coexistence of high mono-methylation and low tri-methylation levels of lysine 4 of histone H3 is considered a signature of enhancers, but a comprehensive view of histone modifications associated to enhancers is still lacking. By combining chromatin immunoprecipitation (ChIP) with mass spectrometry, we investigated cis-regulatory regions in macrophages to comprehensively identify histone marks specifically associated with enhancers, and to profile their dynamics after transcriptional activation elicited by an inflammatory stimulation. The intersection of the proteomics data with ChIP-seq and RNA-seq analyses revealed the existence of novel subpopulations of enhancers, marked by specific histone modification signatures: specifically, H3K4me1/K36me2 marks transcribed enhancers, while H3K4me1/K36me3 and H3K4me1/K79me2 combinations mark distinct classes of intronic enhancers. Thus, our MS analysis of functionally distinct genomic regions revealed the combinatorial code of histone modifications, highlighting the potential of proteomics in addressing fundamental questions in epigenetics.